Structure and Evolution of Glycogen Branching Enzyme N-Termini From Bacteria - Wang, Liang; Liu, Qinghua; Hu, Junfeng; Asenso, James; Wise, Michael J.; Wu, Xiang; Ma, Chao; Chen, Xiuqing; Yang, Jianye; Tang, Daoquan (Frontiers in Microbiology, 2019)
In bacteria, glycogen plays important roles in carbon and energy storage. Its structure has been linked with bacterial environmental durability. Among the essential genes for bacterial glycogen metabolism, glgB-encoded branching enzyme GBE plays an essential role in forming α-1, 6-glycosidic branching points, and determines the unique branching patterns in glycogen. Previously, evolutionary analysis of a small sets of GBEs based on their N-terminal domain organisation revealed that two types of GBEs might exist: 1) Type 1 GBE with both N1 and N2 (also known as CBM48) domains and 2) Type 2 GBE with only N2 domain. In this study, we initially analysed N-terminal domains of 169 manually reviewed bacterial GBEs based on hidden Markov models. A previously unreported group of GBEs (Type 3) with around 100 amino acids ahead of N1 domains was identified. Phylogenetic analysis found clustered patterns of GBE types in certain bacterial phyla, with the shorter, Type 2 GBEs predominantly found in Gram positive species, while longer Type 1 GBEs are found in Gram negative species. Several in vitro studies have linked N1 domain with transfer of short oligosaccharide chains during glycogen formation, which could lead to small and compact glycogen structures. Compact glycogen degrades more slowly and, as a result, may serve as a durable energy reserve, contributing to the enhanced environmental persistence for bacteria. We were therefore interested in classifying GBEs based on their N-terminal domain via large-scale sequence analysis. In addition, we set to understand the evolutionary patterns of different GBEs through phylogenetic analysis at species and sequence levels. 3D modeling of GBE N-termini was also performed for structural comparisons. A further study of 9,387 GBE sequences identified 147 GBEs that might belong to the novel Type 3 group, most of which fall into Actinobacteria phylum. We also attempted to correlate glycogen average chain length with GBE types. However, no significant conclusions were drawn due to limited data availability. In sum, our study systematically investigated bacterial GBEs in terms of domain organisations from evolutionary point of view, which provides guidance for experimental study of GBE N-terminal functions in glycogen structure and bacterial physiology.